A Termodinâmica da Vida - Silva, Mayara Gomes da; Costa, Alessandra do Nascimento; Dias, Márcia Adelino da Silva; Luna, Karla Patrícia de Oliveira (Revista Sustinere, 2021)
⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀